Development of label-free light-controlled gene expression technologies using mid-IR and terahertz light - Yamazaki, Hirohito; Sugawara, Ryusei; Takayama, Yurito (Frontiers in Bioengineering and Biotechnology, 2024)
Gene expression is a fundamental process that regulates diverse biological activities across all life stages. Given its vital role, there is an urgent need to develop innovative methodologies to effectively control gene expression. Light-controlled gene expression is considered a favorable approach because of its ability to provide precise spatiotemporal control. However, current light-controlled technologies rely on photosensitive molecular tags, making their practical use challenging. Here, we review current technologies for light-controlled gene expression and propose the development of label-free light-controlled technologies using Mid-infrared (Mid-IR) and Terahertz light.